The influence of corporate social responsibility “communication and activities” on customer satisfaction and loyalty towards hypermarkets in Kuala Lumpur - Ghaffar Kadhim, Kadhim (2022)
As the number of hypermarket outlets in Malaysia continues to grow, they become more sophisticated in their marketing strategy and more competitive in terms of product quality, price, and service, resulting in fierce competition for patrons. This research examines how hypermarkets can attract more consumers by incorporating “CSR” into their marketing strategy. CSR is a type of technology that enables hypermarkets to increase sales while also contributing to customer satisfaction “CS” and customer loyalty “CL”. By utilizing the theory of the Stimulus Organism Response “S-O-R” model, this study adheres to a positivist research paradigm by proposing a conceptual framework that encompasses corporate CSR activities “CSRA” and CSR communication “SCRC” to comprehend their impact on customer satisfaction “CL” and loyalty “CL”. Questionnaires were distributed to Malaysian consumers throughout the state of Kuala Lumpur using a mall-interception technique “Giant, Econsave, NSK, Tesco, Aeon”. 384 consumers responded to the questionnaire. SPSS and SmartPLS were utilised to conduct an analysis of the data collected in this study. The study's findings revealed that all CSR factors had a positive direct relationship with overall CS and CL, which had a sizable influence on hypermarket visit intention. Additionally, it extends the CSR model by including antecedents to the attitude to assess their influence on customers' intention to visit a hypermarket. Indeed, this study discovered that combining CSR with hypermarkets increased CS and CL. On a more practical level, hypermarket managers could use CSR as a strategy for differentiation to attract additional consumers to their stores. Additionally, hypermarket managers should consider factors such as COS, EF, SLPP, TE, CW, PR, A, and SM to determine how these factors affect customer satisfaction and loyalty.